Development of school canteen and school gardens guidelines as prevention against cardiovascular disease - Bernadette Josephine Istiti Kandarina; Yayuk Hartriyanti; Theodola Baning Rahayujati; Arif Rahmat Kurnia (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Cardiovascular diseases are considered as the deadliest diseases in the world. According to WHO data, deaths caused by coronary heart disease in Indonesia reached 138,380 or 9.89% of the total deaths. The age adjusted mortality rate is 82.30 per 100,000 population with Indonesia ranked #97 in the world. Kulon Progo Regency is located in the western part of the Special Region of Yogyakarta. The average monthly food expenditure in Kulon Progo is Rp365,012 (27.49). While a healthy diet is known and promoted to benefit health, only a small portion is used to buy fruits and vegetables (2.24% and 1.76%). Cardiovascular disease is the main cause of morbidity in Kulon Progo. This study aimed to examine the process of developing guidelines for healthy school canteens and school gardens and promote fruit and vegetable consumption. This study used a qualitative research design. The data were collected through in-depth interviews and focus group discussions. A preliminary survey was conducted in 10 private and public schools in Kulon Progo district, Yogyakarta Province, Indonesia. Guidelines related to healthy lifestyles through Canteen- and school garden were successfully arranged for in-school programs. Interviews and focus group discussions explored possibilities of permanently establishing the programs with local and national funding. Some disagreement was voiced concerning the loss of revenue incurred by local food vendors. Stakeholder involvement is crucially important for the preparation and development of the school canteen - and school gardens guidelines. Follow-up is recommended to carry out the dissemination of the guidebook.